Androgen deprivation therapy and cardiovascular risk: No meaningful difference between GnRH antagonist and agonists—a nationwide population-based cohort study based on 2010–2013 French Health Insurance data. (May 2017) - Scailteux, Lucie-Marie; Vincendeau, Sébastien; Balusson, Frédéric; Leclercq, Christophe; Happe, André; Le Nautout, Béranger; Polard, Elisabeth; Nowak, Emmanuel; Oger, Emmanuel
Abstract: Background: Observational studies suggested that androgen deprivation therapy (ADT) is associated with an increased cardiovascular (CV) risk. They all compared ADT-treated cancer patients to non-treated patients or non-cancer subjects. Our aim was to evaluate whether CV risk differs by type of ADT. Methods: Through nationwide population-based claims reimbursement database linked to hospital discharge database, we identified adult men with prostate cancer who initiated ADT (gonadotrophin releasing hormone [GnRH] agonist or antagonist, antiandrogen [AA], combined androgen blockade [CAB]) or had orchiectomy (OT) between 1st July, 2010, and the 31st December, 2011, and followed them up to 31st December, 2013. The main analysis followed an 'on-treatment' approach that censored all patients at the time of first therapeutic modification; it used Cox regression analysis to estimate hazard ratios (HRs) for hospitalisations for ischaemic events (myocardial infarction or ischaemic stroke, whichever came first), adjusted on age, baseline co-morbidities and taking into account death as a competing risk. Results: Among the 35, 118 new ADT users, 71% received GnRH agonist (reference group), 12% CAB, 13% AA, 3.6% GnRH antagonist and 0.6% had OT. CAB was associated with an increased risk (adjusted HR [95% confidence interval CI], 1.6 [1.3–2.0]) and AA with a decreased risk (adjusted HR [95% CI], 0.6 [0.4–0.9]) of ischaemic events when compared to GnRH agonist. No significant association was found with GnRH antagonist (adjusted HR [95% CI], 1.2 (0.7–2.1)). Conclusion: CV risk appeared different across ADT modalities. The probability of a clinically meaningful difference when comparing GnRH antagonists to agonists appears rather low. In a context where better overall and cancer specific survival without worsening quality of life is a challenge for clinicians, a potential heterogeneity in CV morbidity becomes crucial when choosing an ADT. Highlights: Clinically meaningful heterogeneity as regards ischaemic events across androgen deprivation therapies. Compared to gonadotrophin releasing hormone (GnRH) agonist, combined androgen blockade is strongly detrimental. Compared to GnRH agonist, antiandrogens have better profile. Low probability of a clinically meaningful difference when comparing GnRH antagonists to agonists.